Internationalisation Local Government in the Era of Bureaucracy Reform - Fauzi, Teddy Hikmat (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: Deteriorating performance of the bureaucracy in Indonesia are pessimistic effect on the readiness of the government apparatus to compete in the global dynamics that are supposed to give a greater role for the establishment of bureaucratic reform. In relation to the governance reform is this relevant to the status of local government administration in order to improve the efficiency, effectiveness, and accountability of public sector absolutely must be supported by the implementation of regional autonomy to the maximum capacity and the role of regional resources to proactively explore the potential of the area. Deal with situations and conditions as well as changes in the global dynamics of each area encourages restructuring, revitalization and recreation of as part of regional efforts to create competitive advantage in the era of global competition towards the global learning organization (Marquads and Reynolds, 1994). The occurrence of global democracy as artikuliasi a paradigmatic shift of thinking related to regional autonomy and representation deglobalization liberalization of local government that provides more space for the area to build their regional response observed and utilize current global environmental change, which is based on the ability of local governments to utilize intangible assets in the form of concept, competence and connection (Kanter, 1995). Keywords: Internationalisation Local Government, Bureaucracy Reform